2013
DOI: 10.1007/s10826-013-9756-8
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training Outcomes Among Young Children with Callous–Unemotional Conduct Problems with or at Risk for Developmental Delay

Abstract: School-aged children with conduct problems and high levels of callous-unemotional (i.e., lack of empathy, guilt, and lack of caring behaviors) traits (CP+CU) tend to yield less benefit from traditional interventions than do their low-CU counterparts, particularly with respect to CP outcomes. To date, little is known about treatment response among young children with CP+CU, particularly those with or at risk for developmental delay. Components of Parent-Child Interaction Therapy (PCIT), a parent training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 68 publications
0
19
2
2
Order By: Relevance
“…CU behaviors were assessed using a five-item measure (“shows lack of guilt after misbehavior”, “seems unresponsive to affection”, “shows too little fear”, “punishment doesn’t change behavior” and “shows a lack of affection to others”), previously shown to factor separately from other dimensions of externalizing behavior (i.e., oppositional and attention-deficit behaviors) in five independent samples of children during the age period from 2–4 years old, including in the current sample (Kimonis, Bagner, Linares, Blake, & Rodriguez, 2014; Waller, Hyde et al, 2015; Waller, Shaw et al, 2015; Willoughby, Waschbusch, Moore, & Propper, 2011; Willoughby, Mills-Koonce, Gottfredson, & Wagner, 2014). Moreover, in support of its construct and predictive validity, CU behaviors as measured with these items have been uniquely related to lower parent-reported moral regulation, empathy, and guilt (Waller, Hyde et al, 2015), and predicted more teacher-reported externalizing problems at ages 6 (Waller, Hyde et al, 2015) and 10 (Song, Waller, Hyde, & Olson, 2015) within the current sample.…”
Section: Methodsmentioning
confidence: 82%
“…CU behaviors were assessed using a five-item measure (“shows lack of guilt after misbehavior”, “seems unresponsive to affection”, “shows too little fear”, “punishment doesn’t change behavior” and “shows a lack of affection to others”), previously shown to factor separately from other dimensions of externalizing behavior (i.e., oppositional and attention-deficit behaviors) in five independent samples of children during the age period from 2–4 years old, including in the current sample (Kimonis, Bagner, Linares, Blake, & Rodriguez, 2014; Waller, Hyde et al, 2015; Waller, Shaw et al, 2015; Willoughby, Waschbusch, Moore, & Propper, 2011; Willoughby, Mills-Koonce, Gottfredson, & Wagner, 2014). Moreover, in support of its construct and predictive validity, CU behaviors as measured with these items have been uniquely related to lower parent-reported moral regulation, empathy, and guilt (Waller, Hyde et al, 2015), and predicted more teacher-reported externalizing problems at ages 6 (Waller, Hyde et al, 2015) and 10 (Song, Waller, Hyde, & Olson, 2015) within the current sample.…”
Section: Methodsmentioning
confidence: 82%
“…All items are rated on a three-point scale. Items were selected based on inclusion in CU traits measures in other studies [41][42][43][44] . We have previously created CU traits latent factor scores on this sample at ages 2.5, 3.5, and 5 years 45 by subjecting items to exploratory and confirmatory factor analyses in MPlus 46 .…”
Section: Cu Traitsmentioning
confidence: 99%
“…Items were drawn from four different child problem behaviour scales, shown in Table 1. Items were selected based on inclusion in CU traits measures in other studies (Dadds et al, 2005;Hyde et al, 2013;Kimonis et al, 2014;Willoughby et al, 2011) and relevance to the CU traits construct, with a focus on items assessing lack of concern for others, lack of guilt and poverty of affect. All six items from the CU subscale of the APSD were selected for use at both time points (2.5 years and 5.0 years).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies of early childhood have reported unsatisfactory Cronbach's Alpha for their measures. For example, α = .54 reported for the APSD from a sample of 2-5 year olds (Kimonis et al, 2006) and α = .55 to .66 reported for CBCL-based CU traits measure in four samples of 3-4 year olds (Kimonis, Bagner, Linares, Blake & Rodriguez, 2014;Waller et al, 2015;Willoughby et al, 2011;Willoughbly et al, 2014). In the only investigation to assess the psychometric properties of a CU traits measure in 2 year olds, Hyde et al (2013) reported an unsatisfactory Cronbach's Alpha at age 2 years (α = .57 for primary caregiver and α = .47 for alternative caregiver report), which was slightly improved by age 3 years (α = .64 and α = .66) and approaching commonly accepted values for both reporters at age 4 (α = .72 and α = .66) for their 5 item hybrid measure.…”
Section: Reliability Of Cu Traits Measures In Early Childhoodmentioning
confidence: 99%